Stabilization of dynamic-algebraic Boolean control networks via state feedback control. Issue 13 (September 2018) - Yang, Xingyue; Chen, Bingquan; Li, Yuanyuan; Liu, Yang; Alsaadi, Fuad E.
Abstract: In this paper, we study the state feedback stabilization of dynamic-algebraic Boolean control networks (DABCNs). Using a novel normalization approach, we present necessary and sufficient conditions for the feedback stabilization of DABCNs, and a construction method for the corresponding feedback controllers is proposed. Reduced order feedback stabilization is also studied in this paper. Two examples are given to illustrate the obtained results.